Elaboración de una Guía de Ética y Conducta Profesional para Gerentes de Proyectos de Ingeniería en Colombia (2019)
The document contains an investigation to elaborate a code of ethics and professional conduct applicable to engineering project managers in Colombia whose final product is a guide that consolidates suggested principles, values ​​and competencies for project managers of small and medium-sized companies and for engineering unions. The guide also includes: the suggested structure for the implementation of the code of ethics and professional conduct; the justification and step-by-step process with tools and indicators for monitoring and controlling the effectiveness of the code; and a model for decision-making for project managers when faced with ethical dilemmas in the exercise of the profession, in order to allow them to assess the consequences and choose actions supported in ethical reasoning.